Publishing Patterns of Health Informatics in Africa: A Bibliometric Analysis - Enakrire, Rexwhite Tega (Electronic journal of knowledge management : EJKM, 2021)
This study investigates the publishing patterns of health informatics (HIs) in Africa, with a view to analyse the bibliometric growth. The application of HIs has played an important role in the advancements in medical practice and scholars/academics’ teaching and learning at higher education institutions. The aim of analysing the volume of publications of HIs was to establish the research impact, visibility and output of academics, in order to promote scholarly communication and knowledge sharing, and contribute to existing knowledge in this field of study. Interpretive document analysis was applied to literature extracted from the Scopus database for the period between 1987 to 2018. The keywords entered for search engine optimisation were “Health Informatics” and “Africa”. The duration of the study - from when data was harvested, collated and analysis to when the data was presented in tables and then discussed - was three weeks. The results obtained revealed that there were 2332 papers published within this period. The publications were communicated through different avenues, including articles, conference papers, review and others. Publications on medicine was at the top of the list of subject areas recorded. The top journal, where papers in HIs were published, is Plos One. South Africa was among the top countries that published research on HIs. In relation to institution affiliation, University of Cape Town was identified as the higher education institution that produced the highest number of publications, with 128 publications. In terms of funding bodies that supported research, thus leading to publication of papers in HIs, it was found that the National Institute of Health, South African Medical Council, United States Agency for International Development, Bill and Melinda Gates Foundation, National Institute of Allergy and Infectious Diseases, National Research Foundation played crucial roles.